Nanofibrous bio-inorganic hybrid structure formed through self-assembled peptide (FKFSFEFEFKFK): article - Mohamed Sabib, Masdiana; Tan, Huey Ling; Mulana, Farid (2017)
These research was conducted to study synthesize of the hydroxyapatite (HAP) and characterize the nanoparticles structures and to synthesize the nanofibrous hybrid structure formed through self- assembled peptide (FKFSFEFEFKFK) with HAP as inorganic material. At the same time, these research was conducted to characterize and analysis the morphology of nanofibrous hybrid structure formed through self- assembled peptide (FKFSFEFEFKFK) with water and sodium perchlorate. Furthermore, the method of these research divided into two section; first, the preparation of HAP and concentrated HAP with peptides and second section is characteristic of HAP and HAP with peptide (FKFSFEFEFKFK). Simple precipitation method is used to prepare HAP and the preparation of HAP with peptide (FKFSFEFEFKFK) prepared by using sodium perchlorate salt and water. By using several equipment such as Scanning geology microscope, Fourier Transform Infrared Spectroscopy (FT-IR), Inductive Coupling Plasma (ICP) and Powder X-ray Diffraction (XRD); the nanoparticle can be characterized. By conducting the research, we can better understand the effects of surface charge on cellular uptake and biocompatibility of HAP nanoparticles. Moreover, the mechanical properties of HAP and the surface area of HAP by combination with self-assemble peptide (FKFSFEFEFKFK) can be improved by further study about the HAP nanoparticles